Quantification of seven microbial volatile organic compounds in human serum by solid-phase microextraction gas chromatography-tandem mass spectrometry. (March 2021) - Wazeerud-Din, Idris J.; Silva, Lalith K.; Smith, Mitchell M.; Newman, Cody A.; Blount, Benjamin C.; De Jesús, Víctor R.
Abstract: Microbial volatile organic compounds (MVOCs) are primary and secondary metabolites of fungal and bacterial growth. Changes in environmental conditions (e.g., humidity, light, oxygen, and carbon dioxide) influence microbial growth in indoor environments. Prolonged human exposure to MVOCs has been directly associated with sick building syndrome (SBS), respiratory irritation, and asthma-like symptoms. However, no method exists for assessing MVOC exposure by quantifying them in human serum. We developed a novel, high-throughput automated method for quantifying seven MVOCs (3-methylfuran, 2-hexanone, 2-heptanone, 3-octanone, 1-octen-3-ol, 2-ethyl-1-hexanol, and geosmin) in human serum. The method quantifies the target analytes using solid-phase microextraction gas chromatography-tandem mass spectrometry at low parts-per-billion levels. Limits of detection ranged from 0.076 to 2.77 μg/L. This method provides excellent linearity over the concentration range for the analytes, with coefficients of determination >0.992. Recovery in human serum was between 84.5% and 113%, and analyte precision ranged from 0.38% to 8.78%. The intra-day and inter-day reproducibility showed coefficients of variation ≤11% and ≤8%, respectively. Accurate and precise quantification of MVOCs is necessary for detecting and quantifying harmful human exposures in environments with active microbial growth. The method is well suited for high-throughput analysis to aid investigations of unhealthy exposures to microbial emissions. Graphical abstract: Image 1 Highlights: This study describes a novel SPME-MS/MS method for quantifying seven MVOCs in human serum. This high-throughput method achieved high sensitivity, reproducibility, accuracy, and stability, with ppb detection limits. This method is suitable for assessing potentially harmful human exposures to MVOCs.